LRP6 High Bone Mass Characterized in Two Generations Harboring a Unique Mutation of Low‐Density Lipoprotein Receptor‐Related Protein 6. (2nd March 2023) - Whyte, Michael P; Mumm, Steven; Baker, Jonathan C; Zhang, Fan; Sedighi, Homer; Duan, Shenghui; Cundy, Tim
ABSTRACT: Osteoblast Wnt/ β ‐catenin signaling conditions skeletal development and health. Bone formation is stimulated when on the osteoblast surface a Wnt binds to low‐density lipoprotein receptor‐related protein 5 (LRP5) or 6 (LRP6), in turn coupled to a frizzled receptor. Sclerostin and dickkopf1 inhibit osteogenesis if either links selectively to the first β‐propeller of LRP5 or LRP6, thereby disassociating these cognate co‐receptors from the frizzled receptor. Sixteen heterozygous mutations identified since 2002 within LRP5 and three heterozygous mutations identified since 2019 within LRP6 prevent this binding of sclerostin or dickkopf1 and account for the exceptionally rare, but highly instructive, autosomal dominant disorders called LRP5 and LRP6 high bone mass (HBM). Herein, we characterize LRP6 HBM in the first large affected family. Their novel heterozygous LRP6 missense mutation (c.719C>T, p.Thr240Ile) was present in two middle‐aged sisters and three of their sons. They considered themselves healthy. Their broad jaw and torus palatinus developed during childhood and, contrary to the two previous reports of LRP6 HBM, the appearance of their adult dentition was unremarkable. Skeletal modeling, defined radiographically, supported classification as an endosteal hyperostosis. Areal bone mineral density (g/cm 2 ) of the lumbar spine and total hip featured accelerated increases reaching Z ‐scores of +8 and +6, respectively, although biochemical markers of bone formation were normal. © 2023 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.